Don Quijote ako idiot (Don Quixote as an idiot) - Juraj Dragašek (Ostium, 2018)
The topic of the paper is an accentuation and analysis of moral message of Cervantes’ character of Don Quixote. The aim of the interpretation is to advert that the absurdity of knight-errant could be used as a demonstration of idealistic conviction in personal and also in public life. The article also concerns with the fact that idealism necessary collides with its realistic background and opposite. This collision does not prove that the idealism or realism is true or false. It concerns rather with steadiness, integrity and straightness of the subjective conviction which, however, must be proved in every single case. The paper is also focused on a context of other Cervantes’ works, which rather complicates than helps the interpretation. In the text I also rely on some works and ideas of Dostoyevsky and Schelling. Especially Dostoyevsky was the author who particularly elevates the beauty of Don Quixote.